IMPLEMENTASI DUKUNGAN PERSONAL HYGIENE PADA LANSIA DENGAN DEFISIT PERAWATAN DIRI YANG MENDERITA PENYAKIT OSTEOARTHRITIS DI UPTD PELAYANAN SOSIAL LANJUT USIA BINJAI - Nina Olivia; Sartika Rahma; Muchti Yuda (SINERGI : Jurnal Riset Ilmiah, 2026)
Osteoarthritis (OA) in older adults can cause pain, limited mobility, and self-care deficits, thereby interfering with the ability to maintain personal hygiene. Self-care deficits may lead to impaired fulfillment of basic daily needs and reduced quality of life. This study aimed to describe the implementation of personal hygiene education and training for older adults with self-care deficits who have osteoarthritis at the Binjai Elderly Social Service Center (UPTD Pelayanan Sosial Lanjut Usia Binjai). This study employed a descriptive design using a nursing care approach, which included the stages of assessment, nursing diagnosis, intervention, implementation, and evaluation. The intervention was conducted over three days through mentoring, health education, and observation involving two older adult participants experiencing self-care deficits. The Barthel Index was used to assess the participants' ability to perform personal hygiene independently. The results showed that the participants' Barthel Index scores improved from 16 and 15 at baseline to 19 and 18 after the intervention, indicating an improvement to a mild level of dependency. In addition, the intervention enhanced the older adults' knowledge, practical skills, self-confidence, and independence while reducing their dependence on others in performing personal hygiene activities. The findings are expected to serve as a reference for older adults with osteoarthritis in implementing appropriate personal hygiene practices and may also contribute to the development of standard operating procedures for nursing and healthcare services.